Do skin suits increase average skating speed? - Kuper, G. H.; Sterken, E. (2004)
We analyze the effectiveness of speedskating suits to increase average skating speed at the 2002 Olympic winter games of Salt Lake City. We model the average skating speed of male and female speed skaters at distances from 500 to 10000 meters. Speed not only depends on physical characteristics of the skaters, but also on previous performance and speedskating suits that reduce drag. We find that one specific suit, the so-called Swift Skin suit, significantly increases average skating speed, especially in long-distance events. This suits increase speed by up to 0.2-0.3 seconds per lap on a 400-meter oval. The effects are more pronounced for men than for women and show up in the first part of the race.